2010
DOI: 10.5194/amtd-3-2013-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Near-infrared laser desorption/ionization aerosol mass spectrometry for measuring organic aerosol at atmospherically relevant aerosol mass loadings

Abstract: A new method, near-infrared laser desorption/ionization aerosol mass spectrometry (NIR-LDI-AMS), is described for the real time analysis of organic aerosols at atmospherically relevant total mass loadings. Particles are sampled with an aerodynamic lens onto an aluminium probe and moderate energy NIR laser pulse at 1064 nm is directed onto the probe to vaporize and ionize particle components. Delayed pulse extraction is then used to sample the ions into a reflectron time of flight mass spectrometer for chemical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Details for alignment of the particle beam to the Al probe are described elsewhere. 39,43 Typical aerosol masses sampled were in the range of 1−20 ng. Following particle collection, desorption and ionization were performed by a single 1064 nm laser pulse (5 ns) from a Nd:YAG laser (Brio, Quantel USA, Big Sky, CO) and a time-of-flight mass spectrometer was used for chemical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details for alignment of the particle beam to the Al probe are described elsewhere. 39,43 Typical aerosol masses sampled were in the range of 1−20 ng. Following particle collection, desorption and ionization were performed by a single 1064 nm laser pulse (5 ns) from a Nd:YAG laser (Brio, Quantel USA, Big Sky, CO) and a time-of-flight mass spectrometer was used for chemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Direct online soft ionization aerosol mass spectrometry (AMS) is a sensitive technique to assess SOA formation at a molecular level. , In this study we use metal-assisted near-infrared laser desorption/ionization (NIR-LDI) AMS , to characterize SOA generated from dominant GLVs, their mixtures, and GLVs directly emitted from grass clippings. Recently, Harvey et al identified dominant GLVs from headspace analysis of grass clippings and quantified their relative emission rates.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk chemical properties (O:C, H:C) were measured using an Aerodyne high-resolution timeof-flight mass spectrometer (HR-ToF-AMS), 28,29 according to Chen et al 30 Molecular-level chemical analysis of SOA was performed using near-IR laser desorption/ionization aerosol mass spectrometry (NIR-LDI-AMS). 31,32 A brief description of NIR-LDI-AMS can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The relative intensities of these bands in the two GLV-SOA systems suggest that CHA-SOA contains a greater fraction of carbonyl moieties than HXL-SOA. Using NIR-LDI-AMS, 31,32 the relative abundance of these species was compared between chemical systems. By summing the area of each spectral peak corresponding to carbonyl-containing species (as identified by Jain et al 39 ) and normalizing to the total area of the mass spectrum, the "carbonyl contribution" to CHA-SOA (3.7 ± 0.8%) was found to be statistically greater than that of HXL-SOA (2.1 ± 0.5%).…”
Section: Assignment Of Spectral Features Tomentioning
confidence: 99%
“…9 Therefore, recent instrumental developments focus on softer ionization techniques such as atmospheric pressure chemical ionization (APCI-MS), 11,12 extractive electrospray ionization (EESI-MS), 13 or near-infrared (IR) laser desorption ionization. 14 Yet unexplored in aerosol research are the latest developments in soft ionization techniques that have been made during the advent of ambient desorption/ionization mass spectrometry (ADI-MS). The newly developed ionization techniques comprise ion sources such as the low temperature plasma probe (LTP), 15 the DART source, 16 the flowing atmosphericpressure afterglow (FAPA) source, 17 or the desorption electrospray ionization (DESI) source.…”
Section: ■ Introductionmentioning
confidence: 99%